Implementation of a performance-based financing scheme in Malawi and resulting externalities on the quality of care of non-incentivized services - Brenner, Stephan; Favaretti, Caterina; Lohmann, Julia; Chinkhumba, Jobiba; Muula, Adamson S.; De Allegri, Manuela (BMC pregnancy and childbirth, 2021)
Countries in Africa progressively implement performance-based financing schemes to improve the quality of care provided by maternal, newborn and child health services. Beyond its direct effects on service provision, evidence suggests that performance-based financing can also generate positive externalities on service utilization, such as increased use of those services that reached higher quality standards after effective scheme implementation. Little, however, is known about externalities generated within non-incentivized health services, such as positive or negative effects on the quality of services within the continuum of maternal care.